Pendampingan Tata Kelola Manajemen Badan Usaha Milik Lembang (BUMlem) Batu Rumbuk Dalam Memberdayakan dan Kemandirian Masyarakat Lembang Ma’kuanpare Kabupaten Toraja Utara - Lusdani, Westerini; Pagiu, Chrismesi; Pundissing, Rati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The success factors for Village Owned Enterprises (BUMLem) are human resource management. So far, the quality of human resources or managers working at BUMLem is generally still very low, this is indicated by the still low quality of products, limited ability to develop new products, slow application of technology, and weak business management. The purpose of this activity is to support the development and progress of existing businesses in Lembang in particular. The method in this service begins with initial research (initial assessment) of problems and helping problems is carried out with focus group discussion (FGD) activities both with BUMLem Batu Rumbu administrators, village heads and the local community. It is hoped that the results of assisting BUMLem management governance will increase community income. It is hoped that in the future BUMLem will be able to carry out functional governance management including human resource governance, production and marketing. BUMLem is able to be more mature and wise in responding and quickly finding solutions to any problems that occur when the business is growing.